Exploration of sensory and spinal neurons expressing gastrin-releasing peptide in itch and pain related behaviors - Devin M. Barry (Nature Portfolio, 2020)
The role of gastrin related peptide (GRP+) neurons in itch is debated. Here, the authors generate a conditional knock-in mouse to label and manipulate GRP expressing DRG neurons and investigate their role in itch and nociception.